On Splitting Wood and Lifting Stones: Finding Jesus in Australia - Winter, Sean (Journal for the Academic Study of Religion, 2022)
One early Christian gospel attributes the following saying to Jesus: ‘I am the light who is above all things… Split a piece of wood—I am there. Lift the stone, and you will find me there’ (Gospel of Thomas 77). The aphorism suggests both the possibility of finding Jesus in ordinary, and therefore surprising, places, and the human labour that might lead to revelation. As such, it stands as a suggestive metaphor for the scholarly industry and instincts of this issue’s articles that chart the Christ-figure in Australian imagination. Drawing on biblical reception history and the arguments and strategies of these articles, I suggest that while Christian theology traditionally affirms Christ as universal redeemer (‘the light who is above all things’), these articles are a reminder that it is only inside and under the highly particular trees and rocks of locality, land and culture that Jesus will be found.